2021
DOI: 10.1519/ssc.0000000000000665
|View full text |Cite
|
Sign up to set email alerts
|

Practical Strategies for Integrating Strength and Conditioning Into Early Specialization Sports

Abstract: Early sport specialization involves physically immature children participating in intensive year-round training and/or competition for a single sport. The lack of sport exposure and diversification during the developmental years may underlie the increased risk of overuse injuries, blunting of motor skill development, psychosocial issues, overtraining syndrome, burnout, and potential dropout from sport. With increasing number of youth choosing, or being encouraged, to specialize at an early age, we aim to provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 85 publications
0
12
0
Order By: Relevance
“…However, sport does not always positively affect children and adolescents. The world’s tendency for early specialization especially leads to dangerous consequences when immature children participate in intensive all-year-round training and competition in a single sport [ 3 ]. The lack of diversification and exposure to different sports activities during the developmental periods may underlie the enhanced risk of injuries, stopping motor skill development, psychosocial problems, overtraining syndrome, and a high possibility of burnout and potential dropout from sports [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, sport does not always positively affect children and adolescents. The world’s tendency for early specialization especially leads to dangerous consequences when immature children participate in intensive all-year-round training and competition in a single sport [ 3 ]. The lack of diversification and exposure to different sports activities during the developmental periods may underlie the enhanced risk of injuries, stopping motor skill development, psychosocial problems, overtraining syndrome, and a high possibility of burnout and potential dropout from sports [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The lack of diversification and exposure to different sports activities during the developmental periods may underlie the enhanced risk of injuries, stopping motor skill development, psychosocial problems, overtraining syndrome, and a high possibility of burnout and potential dropout from sport. Moreover, children who are early specialized in one selected sports discipline are deprived of the opportunity to increase their self-esteem by naturally trying different activities and hobbies [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…These are the sports of early specialization (attractive especially for girls) in which children undergo comprehensive and intense sports training [ 2 , 3 ]. Scientific studies have shown that the skills and competences acquired during gymnastic training and competitions have a positive effect on the physical [ 4 , 5 , 6 , 7 , 8 , 9 , 10 ], mental [ 11 ], social [ 1 ], and cognitive [ 12 , 13 ] development of a child.…”
Section: Introductionmentioning
confidence: 99%